2014
DOI: 10.1159/000375466
|View full text |Cite
|
Sign up to set email alerts
|

Thrombolysis in Chinese Ischemic Stroke Patients with Renal Dysfunction

Abstract: Background: Current data concerning the relationship between renal function and clinical outcome among stroke patients treated with intravenous thrombolytic therapy are conflicting. Our aim is to analyze whether the clinical outcome of Chinese ischemic stroke patients treated with thrombolytic therapy is affected by the presence of renal dysfunction. Methods: Chinese patients who received intravenous thrombolytic therapy for acute ischemic stroke were recruited. Renal dysfunction was defined as an estimated gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 30 publications
2
10
0
Order By: Relevance
“…However, multivariate regression analysis revealed that lower GFR was not an independent factor for poor outcome (mRS 3-6) after thrombectomy in our large consecutive cohort. These findings are in accordance with several previous analyses on the impact of RD in ischemic stroke patients treated with rtPA that did not find an independent association between RD and poor clinical outcome [7,8,9]. Yet, factors that were independently associated with poor outcome in our cohort were higher age, higher morbidity, and stroke-related factors, including higher initial NIHSS values and particularly poor recanalization rates.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…However, multivariate regression analysis revealed that lower GFR was not an independent factor for poor outcome (mRS 3-6) after thrombectomy in our large consecutive cohort. These findings are in accordance with several previous analyses on the impact of RD in ischemic stroke patients treated with rtPA that did not find an independent association between RD and poor clinical outcome [7,8,9]. Yet, factors that were independently associated with poor outcome in our cohort were higher age, higher morbidity, and stroke-related factors, including higher initial NIHSS values and particularly poor recanalization rates.…”
Section: Discussionsupporting
confidence: 93%
“…Overall, RD was present in 20.2% of our patients; and similar to other series [3,6,7], we observed that patients with RD were older and more often suffered from hypertension, hypercholesterolemia, previous strokes, coronary heart disease, and atrial fibrillation than patients with normal renal function. Despite higher morbidity, stroke severity did not differ between patients with and without RD in our group of thrombectomy patients, a finding that is inconsistent with the results of previous studies [3,26,27].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations